Cu(I)‐catalyzed Green Synthesis of Propargyl Amines Decorated with Carbazole Moiety by A3 ‐Coupling. Issue 7 (18th May 2017) - Shehzadi, Syeda Aaliya; Saeed, Aamer
Abstract : A series of novel N ‐alkylcarbazol–propargylamine hybrids were designed and synthesized by Cu I Br‐catalyzed A 3 ‐coupling of N ‐octylcarbazol‐3‐carbaldehyde, amines, and alkynes. The tri‐substituted propargyl amines decorated with carbazole moiety were obtained under solvent‐free conditions in good to moderate yields. Furthermore, the scope of the method was studied, which was found to be applicable to primary aliphatic and aromatic amines. Also, a large variety of substituents both on alkynes and anilines are well tolerated. Abstract : During the last decade, the A 3 ‐coupling reaction emerged as a powerful tool to construct propargylamines with desirable structural units. Although it has covered many functional groups, still efficient, mild, and green conditions to achieve highly biologically attractive structural motifs remain attractive.